The Influence of Service Quality and Employee Performance on Customer Satisfaction at the Contact Centre Unit of PT. Astra Honda Motor Jakarta - Susriyati, Istiyani; Sahim, Aswin Naldi; Rohayati, Yeti (STIE Indonesia Banking School, 2025)
In today’s competitive business landscape, service quality and employee performance are critical determinants of customer satisfaction, especially within contact centre environments. This study investigates the simultaneous impact of service quality and employee performance on customer satisfaction at PT Astra Honda Motor’s (AHM) Contact Centre. Using a quantitative approach with descriptive and verificative methods, data were collected from 100 customers who interacted with the Contact Centre between October 2024 and January 2025. The research employed a structured questionnaire with a 5-point Likert scale and analyzed data using SPSS version 25. Results from the t-test show that both service quality and employee performance have a significant and positive partial effect on customer satisfaction. Furthermore, the F-test confirms their simultaneous influence, with a coefficient of determination (R²) of 0.214, indicating that 21.4% of the variance in customer satisfaction can be explained by the two variables. These findings are supported by previous studies and emphasize the importance of responsiveness, reliability, competence, and communication in enhancing customer experience. The study concludes that improving service delivery and empowering employees are essential strategies for increasing customer satisfaction and fostering loyalty in competitive service-driven industries like